Factors Causing Anxiety in Speaking English Experienced By The Students of Senior High School in Jombang - Maisarah Maisarah (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2019)
Abstract This study was conducted to know the factors contributing to the anxiety in speaking English experienced by students of a high school in Jombang. This study identified the factors of anxiety in speaking English based on the phenomenon experienced by the students. The research method used in this study was descriptive quantitative. Ten students who felt anxious in speaking were chosen as respondent based on the results of the questionnaire from preliminary study.The research instruments used in the data collection was questionnaire. While the data analysis was the frequency distribution analysis (percentage of occurrence).The result shows that there were three factors that cause anxiety in speaking the factors were: communication apprehension, test anxiety, and negative evaluation. The results of this study showed that the first factor had the most influenced on students' anxiety in speaking English was the communication apprehension which was the strongest factor causing the students’ anxiety in speaking. The second was the test Anxietyand the last one is the fear of being evaluated negatively.